Bank Selection Criteria and Performance of Public and Private Banks of Sri Lanka: A Comparative Study - M. S. Nilam (CenRaPS Journal of Social Sciences, 2020)
Financial deregulation and technological advancement have led the sri lankan banking industry to highly competitive environment. In sri lanka, the competition is not only among the local banks, but also from foreign banks. To stay competitive and strong, a bank’s customer retention is crucial. In this context banking institutions would like to know how the customers select their bank and how they perceive the performance of banks in such competitive environment. The researcher selected sample of 468 banking customers from public and private banks of sri lanka. Responses were analyzed and presented through descriptive, correlation and regression analysis. The findings showed that the security and service quality were the two most crucial factors when selecting a bank in sri lanka. Significant gender and education level factors in bank selection were observed. Study concludes that sri lankan private banks perform better on those factors than the public banks in sri lanka.